NEW MARKERS FOR CARDIOVASCULAR RISK: FROM STUDIES TO CLINICAL GUIDELINES - D. A. Anichkov; N. A. Shostak (Klinicist, 2014)
New markers for cardiovascular disease (CVD) risk are the subject of an intensive discussion in the scientific literature. The biomarkers (newlipid parameters, inflammatory markers) and signs of subclinical atherosclerosis are candidates to be included in models to assess the cumulative risk of CVD. The paper considers the basic studies dealing with new markers of CVD risk and their place in current clinical recommendations.